Effect of different processing conditions on antioxidant activity of Gracilaria edulis(Rhodophyseae) in Sri Lanka - Ganeshamoorthy, Umakanthan (British Journal of Healthcare and Medical Research, 2019)
Gracilaria edulis is red marine algae currently cultivated in Sri Lanka but relatively low than other country such as China and Japan. This species are used to produce drugs and healthy delicious low calorie foods because of they are primary source of secondary metabolite and to be used as natural antioxidants and antimicrobials. The Purpose of this research investigates effect of different processing conditions on antioxidant activity of G.edulis (Rhodophyseae) by hydrogen peroxide scavenging activity assay. Absorbance at 230 nm, hydrogen peroxide scavenging assays were done. Different processed G.edulis such as fresh, steamed, boiled, dried and microwaved were extracted with methanol. Their antioxidant properties were compared to the L-ascorbic acid which used as positive control. The methanolic extracts of this red algae was prepared keeping methanol as a standard. Methanol was used as control. In minitab-15 statistical software package, Paired T-Test was clearly shown the absorbance, inhibition or hydrogen peroxide scavenging activity depend on the processing conditions of the G.edulis methanol extract. This statistical test did tell about the difference between the different processing conditions of the methanol extract of the G.edulis (p<0.05) and antioxidant activity and these were not independent factors such are depend on each other. Hence antioxidant activity or H2O2 scavenging activity was highly in boiled G.edulis, followed by fresh, microwaved, dried and steamed respectively. L-ascorbic acid was used as Positive control and its antioxidant activity was higher than dried and steamed but relatively lowers than microwaved, fresh and boiled G.edulis. Finally Boiled G.edulis sample was recorded prominent antioxidant activity due to leaching of less antioxidant compounds. In future this study is used to functional product development incorporation of dried followed by boiled G. edulis into bakery Products.